Timpuyo a Cultural Center for Laoag City - Agsunod, Deetz Beryl L. (College of Architecture, University of the Philippines Diliman, 2018)
Architecture has always been dynamic, with different styles evolving, and serving as a contradiction and a response to the one before it. Differences in approach and methods brought about different ways of thinking, and although no design is perfect, architecture is often programmed to do its highest potential in its time, serving its users with great ease and comfort. In this project, the method of an Agenda based programming was used in order to create a space that is most suitable to the place where the project will be located. The chosen site is in the city of Laoag, province of Ilocos Norte. Through occular inspections, interviews, and site experience, four agendas were made, namely History and Culture, Community, Education and Livelihhod. The province's local textile, Inabel, was used as an inspiration for the design, borrowing three concepts : connection, comfort, and the use of local products. The people of Laoag and these agendas and concepts created Timpuyog, Laoag City's Cultural Center. Timpuyog aims to be the catalyst for change in the attitude of the community in terms of how they treat their culture. Timpuyog aims to unite the community to celebrate the vibrant culture of the Ilocano people. With its quality facilities, it aims to provide the people of Laoag an avenue to showcase the city's local products and cuisine at the same time educate about the wonders the city has to offer. Ultimately, Timpuyog aims to become a center of Ilocano excellence, a bastion of knowledge where the public, residents and visitors alike, could relentlessly search for the untarnished truth.